Seminal plasma promotes decidualization of endometrial stromal fibroblasts in vitro from women with and without inflammatory disorders in a manner dependent on interleukin-11 signaling. Issue 3 (27th March 2020) - George, Ashley F; Jang, Karen S; Nyegaard, Mette; Neidleman, Jason; Spitzer, Trimble L; Xie, Guorui; Chen, Joseph C; Herzig, Eytan; Laustsen, Anders; Marques de Menezes, Erika G; Houshdaran, Sahar; Pilcher, Christopher D; et al.
Abstract: STUDY QUESTION: Do seminal plasma (SP) and its constituents affect the decidualization capacity and transcriptome of human primary endometrial stromal fibroblasts (eSFs)? SUMMARY ANSWER: SP promotes decidualization of eSFs from women with and without inflammatory disorders (polycystic ovary syndrome (PCOS), endometriosis) in a manner that is not mediated through semen amyloids and that is associated with a potent transcriptional response, including the induction of interleukin (IL)-11, a cytokine important for SP-induced decidualization. WHAT IS KNOWN ALREADY: Clinical studies have suggested that SP can promote implantation, and studies in vitro have demonstrated that SP can promote decidualization, a steroid hormone-driven program of eSF differentiation that is essential for embryo implantation and that is compromised in women with the inflammatory disorders PCOS and endometriosis. STUDY DESIGN, SIZE, DURATION: This is a cross-sectional study involving samples treated with vehicle alone versus treatment with SP or SP constituents. SP was tested for the ability to promote decidualization in vitro in eSFs from women with or without PCOS or endometriosis ( n  = 9). The role of semen amyloids and fractionated SP in mediating this effect and in eliciting transcriptional changes in eSFs was then studied. Finally, the role of IL-11, a cytokine with a key role in implantation and decidualization, was assessed as a mediator of the SP-facilitated decidualization. PARTICIPANTS/MATERIALS, SETTING, METHODS: eSFs and endometrial epithelial cells (eECs) were isolated from endometrial biopsies from women of reproductive age undergoing benign gynecologic procedures and maintained in vitro . Assays were conducted to assess whether the treatment of eSFs with SP or SP constituents affects the rate and extent of decidualization in women with and without inflammatory disorders. To characterize the response of the endometrium to SP and SP constituents, RNA was isolated from treated eSFs or eECs and analyzed by RNA sequencing (RNAseq). Secreted factors in conditioned media from treated cells were analyzed by Luminex and ELISA. The role of IL-11 in SP-induced decidualization was assessed through Clustered regularly interspaced short palindromic repeats (CRISPR)/Cas-9-mediated knockout experiments in primary eSFs. MAIN RESULTS AND THE ROLE OF CHANCE: SP promoted decidualization both in the absence and presence of steroid hormones ( P  < 0.05 versus vehicle) in a manner that required seminal proteins. Semen amyloids did not promote decidualization and induced weak transcriptomic and secretomic responses in eSFs. In contrast, fractionated SP enriched for seminal microvesicles (MVs) promoted decidualization. IL-11 was one of the most potently SP-induced genes in eSFs and was important for SP-facilitated decidualization. LARGE SCALE DATA: RNAseq data were deposited in the Gene Expression Omnibus repository under series accession number GSE135640. LIMITATIONS, REASONS FOR CAUTION: This study is limited to in vitro analyses. WIDER IMPLICATIONS OF THE FINDINGS: Our results support the notion that SP promotes decidualization, including within eSFs from women with inflammatory disorders. Despite the general ability of amyloids to induce cytokines known to be important for implantation, semen amyloids poorly signaled to eSFs and did not promote their decidualization. In contrast, fractionated SP enriched for MVs promoted decidualization and induced a transcriptional response in eSFs that overlapped with that of SP. Our results suggest that SP constituents, possibly those associated with MVs, can promote decidualization of eSFs in an IL-11-dependent manner in preparation for implantation. STUDY FUNDING/COMPETING INTEREST(S): This project was supported by NIH (R21AI116252, R21AI122821 and R01AI127219) to N.R.R. and (P50HD055764) to L.C.G. The authors declare no conflict of interest.